Effect of wave climate change on longshore sediment transport in Southwestern Black Sea - Basaran, Busra; Guner, H. Anil Ari (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
As a result of long-term changes of the wave climate, changes in spatial and temporal scales occur in coastal regions and cause coastal morphology to change. This study investigates the effect of changes in wave climate (wave height, wave period, wave direction) on longshore sediment transport (LST) at Karasu coast, located on the southwestern coast of the Black Sea. European Center for Medium-Range Weather Forecasts (ECMWF) ERAInterim wind data covering the period of 1979-2018 was used to obtain the wave climate of the Southwestern Black Sea coasts and to understand the dynamics of LST throughout the region. Net and gross sediment transport rates were calculated according to three different empirical and one numerical methods by using hourly significant wave heights, peak wave periods and incident wave angles. According to the 40-year wave climate data in the region, the average annual significant wave height is 0.92 m, the peak wave period is 5.53 s and the angle of wave incidence is between N-NNE sector. Waves are composed of two components; swell waves and wind waves and as a result of the study, it has been observed that swell waves have an order of magnitude larger contribution to the LST along the coast than wind waves for the respective research area, by an average factor of 12 and 17 for the net and gross LST rate, respectively. At the end of the 40-year period between 1979 and 2018, according to three different empirical and one numerical LST methods, the average net LST rate along the Karasu coast was 65,000 +/- 5,000 m3/year, while the gross LST rate was 190,000 +/- 20,000 m3/year. When the change of gross LST during the study period was examined, it was observed that an average decrease of 5.6% occurred. This reduction in the LST rate was observed to be associated with a 4.1% decrease in the height of the swell waves at the end of 40 years.
Keywords: Wave climate change; Longshore sediment transport rate; Southwestern Black Sea; Karasu coast; Empirical methods; LITDRIFT; SAND TRANSPORT; VARIABILITY; NEARSHORE; BEACH; PARAMETERS; DEPENDENCE; BREEZE; BAR; Marine & Freshwater Biology; Oceanography